Fan worm polychaetes (Sabellidae: Sabellinae) collected during the Thai-Danish BIOSHELF Project. - Fitzhugh, Kirk (Phuket Marine Biological Center Special Publication, 2002)
A total of 23 Sabellinae species in 12 genera are reported from the Thai–Danish BIOSHELF Project off the west coast of Thailand in the Andaman Sea, Indian Ocean. Of the species collected, only two have been previously described: Chone trilobata Gallardo, originally known only from Viet Nam, and Branchiomma cingulatum (Grube), which has been recorded from the Indo-Pacific. Four new species are described: Euchone cochranae, Jasmineira labrofusca, Laonome andamanensis, and Megalomma multioculatum. Two new genera and species are also described: Panoumethus dubius and Claviramus grubei. Two previously described species, Jasmineira candela (Grube) and J. oculata Langerhans, are shown to belong in Claviramus. Potential new species are informally described in the genera Chone Krøyer (six species), Demonax Kinberg (one species), Euchone Malmgren (one species), Laonome Malmgren (one species), and Megalomma Johansson (one species). Indeterminable species in Euchone, Megalomma, Myxicola Koch in Renier, Notaulax Tauber, and a species incertae sedis, are mentioned. A new continental slope species, Jasmineira lobata, is also described from the deep station of the Thai–Danish BIOSHELF Project off Thailand.
World Polychaeta Database (WPolyDb)